-32f-12g=48

Simple and best practice solution for -32f-12g=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -32f-12g=48 equation:


Simplifying
-32f + -12g = 48

Solving
-32f + -12g = 48

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '12g' to each side of the equation.
-32f + -12g + 12g = 48 + 12g

Combine like terms: -12g + 12g = 0
-32f + 0 = 48 + 12g
-32f = 48 + 12g

Divide each side by '-32'.
f = -1.5 + -0.375g

Simplifying
f = -1.5 + -0.375g

See similar equations:

| 2(9-7s)= | | -5*y=x^2 | | 2r-y-6=0 | | 4k(7k+5)= | | 12b^2-8=6b | | X+(-4)=-7 | | -10+2x=3x-1+8x | | 12b^2-8=ab | | x^2(x+7)=40x+100 | | (y^2)-23y+130=0 | | 7n+20=6 | | 200-6x=500-6x | | 4n+3+20=6 | | -16t^2+5t+92=0 | | Y+-3=8 | | 0=9x+25+5y | | 2.5x+1.2-4=3.5 | | 4-4b+3b=-3-5b+5b | | 9+x+x=29 | | -6x^2-5x+7=0 | | (6x+4)-(9x-4)= | | 12n-7=-2 | | 2(x-1)-5= | | 8y-12x=0 | | 11.70=2.10+0.80x | | 2x^2-150=650 | | -100=2(-8-6r) | | 19=x^2-17 | | (2x^2-7xy+6y^2)= | | 11(2-2x)+4= | | 7(2k+3)= | | 20-x^2=-80 |

Equations solver categories